"The Trees Need Water" and the Students Need Authentic Responsibility: Learning Almost-in-the-Wild in a Community-Based Internship. (2022) - Blum, Susan D.; Hebert, Terri; Robinson, Gabrielle; Gillespie, Kirill; Mallozzi-Kelly, Maeve; Norberg, Melissa
No abstract available